Formulation of nitrendipine/hydroxypropyl-β-cyclodextrin inclusion complex as a drug delivery system to enhance the solubility and bioavailability by supercritical fluid technology. (3rd April 2023) - Liang, Bingchan; Hao, Jianxia; Zhu, Ning; Han, Limin; Song, Lijun; Hong, Hailong
Graphical abstract: Highlights: The inclusion complexes of nitrendipine with hydroxypropyl-β-cyclodextrin (HP-β-CD) were successfully prepared by SEDS technique for the first time. The process parameters were optimized for preparing the inclusion complex. . Significant enhancement in solubility and dissolution of NT was observed. NT/HP-β-CD host–guest inclusion complex could act as a novel drug delivery vehicle. Abstract: In this study, the solution enhanced dispersion by supercritical fluids (SEDS) technology was applied to prepare inclusion complex with hydroxypropyl-β-cyclodextrin (HP-β-CD) as carrier to enhance the oral bioavailability of nitrendipine (NT). The obtained particles were characterized by XRD, SEM, FT-IR, DSC, MS and NMR, which demonstrated the formation of inclusion complex in supercritical CO2 . The phase solubility tests revealed that the complexation of NT with HP-β-CD was established in a 1:1 stoichiometry. The effects of different operating parameters, including the solvent, temperature, pressure, molar ratio, and concentration, on the particle size and dissolution were investigated in detail. The results proved that the SEDS technology markedly improved the solubility and dissolution of NT compared with pure NT and physical mixture. This study provides a theoretical basis for obtaining an inclusion complex with high solubility and low toxicity using SEDS technology.